Liver resection for metastatic uveal melanoma: experience from a supra-regional centre and review of literature. Issue 1 (21st November 2022) - Trivedi, Dharmadev B.; Aldulaimi, Natasha; Karydis, Ioannis; Wheater, Matthew; Modi, Sachin; Stedman, Brian; Karavias, Dimitrios; Primrose, John; Pearce, Neil; Takhar, Arjun S.
Abstract : Management of liver metastases from uveal melanoma (LMUM) requires multimodal approach. This study describes evolution of liver resection for LMUM, reviewing current literature and institutional outcomes. Records of patients referred to the Melanoma Multi-Disciplinary Team between February 2005 and August 2018 were reviewed. All publications describing surgery for LMUM were identified from PubMed, Embase, and Google Scholar. Thirty-one of 147 patients with LMUM underwent laparoscopic liver biopsy, and 29 (14 females) had liver resections. Nineteen liver resections were performed locally [7 major (≥3 seg), 14 laparoscopic] without major complications or mortality. Overall survival positively correlated with the time from uveal melanoma to LMUM (Spearman's rho r s  = 0.859, P  < 0.0001). Overall and recurrence-free survivals were comparable following R1 or R0 resections (OS 25 vs. 28 months, P  = 0.404; RFS 13 vs. 6 months, P  = 0.596). R1 resection cohort had longer lead-time (median 100 vs. 24 months, P  = 0.0408). Eleven publications describing liver resection for LMUM were identified and included in the narrative review. Surgery for LMUM is safe and complements multidisciplinary management. Despite heterogeneity in literature, time from diagnosis of uveal melanoma to LMUM remains a key factor affecting survival after liver resection.